2018
DOI: 10.1016/j.jadohealth.2018.06.033
|View full text |Cite
|
Sign up to set email alerts
|

Reciprocal Associations Between Adolescent Girls’ Chronic Interpersonal Stress and Nonsuicidal Self-Injury: A Multi-wave Prospective Investigation

Abstract: Purpose: Nonsuicidal self-injury (NSSI) is associated with increased risk of suicide attempts. Theories of NSSI assert interpersonal stress as a common risk factor for, and perhaps consequence of, NSSI. Prior research has not examined reciprocal associations between chronic interpersonal stress and NSSI. This study used a multiwave, prospective design to address this gap in a sample of adolescent girls, a group with elevated risk for both chronic interpersonal stress and NSSI. Pubertal development was examined… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
23
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 42 publications
(53 reference statements)
3
23
0
1
Order By: Relevance
“…With regard to the age-15-only association, it is possible that break-ups at that age involve a first serious romantic partner, and therefore a novel kind of stressor. The age-specific pattern is also consistent with prior work, which found that chronic romantic stress (e.g., rejection, arguments, having fewer romantic relationships than one's peers) increased the risk of self-injury among girls with advanced pubertal development (21). However, a caveat is that the items used to assess relationship breakup did not distinguish adolescents who were abandoned by a partner or friend from those who decided to break off the relationship themselves.…”
Section: Contexts Of Stressful Life Eventssupporting
confidence: 85%
See 2 more Smart Citations
“…With regard to the age-15-only association, it is possible that break-ups at that age involve a first serious romantic partner, and therefore a novel kind of stressor. The age-specific pattern is also consistent with prior work, which found that chronic romantic stress (e.g., rejection, arguments, having fewer romantic relationships than one's peers) increased the risk of self-injury among girls with advanced pubertal development (21). However, a caveat is that the items used to assess relationship breakup did not distinguish adolescents who were abandoned by a partner or friend from those who decided to break off the relationship themselves.…”
Section: Contexts Of Stressful Life Eventssupporting
confidence: 85%
“…Adolescents also often face stressful life events as they undergo transitions in their peer networks (peer context), form intimate bonds with best friends and romantic partners (intimate relationships context), and re-negotiate their roles in relation to parents and siblings (family context) (9,20). Evidence of associations between chronic adversity relating to peer and romantic relationships and self-injury is consistent (13,19,21,22), whereas evidence of associations between family-related adversity and self-injury is mixed (21,23,24). Evidence of the unique role of acute life events in these contexts (e.g., being physically attacked by peers, the breakup of intimate relationships, or experiences of loss in the family context) is largely missing from the literature.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The age of onset for NSSI is around 12–14 years [3] and peaks during adolescence, with rates declining in adulthood [8]. Sensitivity to interpersonal stress, high emotional distress and in some cases chronic romantic stress [9] have been suggested to play a role in the development and maintenance of NSSI, with self-injury behavior regulating both affective and social experiences [1]. The fact that interpersonal difficulties commonly precede NSSI has also been noted in the proposed DSM-5 criteria [6].…”
Section: Introductionmentioning
confidence: 99%
“…lifetime prevalence of NSSI is approximately 20% in this population (Swannell, Martin, Page, Hasking, & St. John, 2014;Whitlock, Eckenrode, & Silverman, 2006), with 12month engagement rates varying widely, up to 14% (Kuentzel, Arble, Boutros, Chugani, & Barnett, 2012;Serras, Saules, Cranford, & Eisenberg, 2010;Wilcox et al, 2012). Engagement in NSSI is strongly associated with a wide range of both internalizing and externalizing psychiatric disorders (Nitkowski & Petermann, 2011). Given its high prevalence, as well as increasing evidence suggesting that NSSI is associated with both clinical and functional impairment, the most recent edition of the Diagnostic and Statistical Manual of Mental Disorders-Fifth Edition (DSM-5) incorporated nonsuicidal self-injury disorder (NSSI-D) as a condition requiring further study (American Psychiatric Association, 2013).…”
mentioning
confidence: 99%